Developing the Green Building Materials Selection Criteria for Sustainable Building Projects - Al-Atesh, E.A. (Insight Society, 2021)
The utilization of green building materials (GBMs) becomes necessary. The lack of clear guidelines on utilizing GBMs and difficulties in adjusting GBMs criteria adequately for the three sustainability pillars is a major obstacle. Furthermore, it is an issue of multi-criteria decision that considers all sustainability factors during the selection process and implies multi-criteria decision-making mechanism statistical techniques. Consequently, the main challenge is identifying assessment criteria based on the sustainability concept and prioritizing and consolidating the evaluation framework of relevant criteria. Therefore, this paper aims to determine the selection of GBMs criteria to achieve sustainable building projects in Malaysia. To do so, a total of three key criteria and 32 sub-criteria were identified by a review of the previous literature, accompanied by a semi-structured interview with 12 experts. Data were obtained using a questionnaire from 73 building professionals when exploring the country's GBM criteria using the Exploratory Factor Analysis (EFA). The findings indicate that the associations between these criteria across the EFA have three key components: environmental, economic, and social. A mean and standard deviation scatter plot analysis was also performed to evaluate the data descriptively to define the relevance criteria. Finally, this study strengthens the current management of building engineering by enhancing the criteria for selecting GBMs in the Malaysian construction industry to satisfy the sustainability objectives of the building projects. Â© IJASEIT is licensed under a Creative Commons Attribution-Share Alike 4.0 International License.